2020
DOI: 10.2903/j.efsa.2020.6267
|View full text |Cite
|
Sign up to set email alerts
|

Potential BSE risk posed by the use of ruminant collagen and gelatine in feed for non‐ruminant farmed animals

Abstract: EFSA was requested to estimate the cattle bovine spongiform encephalopathy ( BSE ) risk (C‐, L‐ and H‐ BSE ) posed by ruminant collagen and gelatine produced from raw material fit for human consumption, or from material classified as Category 3 animal by‐products ( ABP ), to be used in feed intended for non‐ruminant animals, including aquaculture animals. Three risk pathways ( RP ) were identified by which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…More significantly, collagen originating from animal sources may be risky for disease transmission. Bovine spongiform encephalopathy (BSE) induced by ruminant collagen for human consumption has been investigated as a featured example [ 240 ]. Also commonly employed in dental surgery are bovine-derived collagen grafts, which might pose hazardous transmission of prion to patients [ 241 ].…”
Section: Future Perspectives and Challengesmentioning
confidence: 99%
“…More significantly, collagen originating from animal sources may be risky for disease transmission. Bovine spongiform encephalopathy (BSE) induced by ruminant collagen for human consumption has been investigated as a featured example [ 240 ]. Also commonly employed in dental surgery are bovine-derived collagen grafts, which might pose hazardous transmission of prion to patients [ 241 ].…”
Section: Future Perspectives and Challengesmentioning
confidence: 99%
“…While a few well-characterised rodent-adapted strains were widely used for decontamination/ inactivation studies at the start of the bovine spongiform encephalopathy (BSE) epidemic, it has subsequently been shown that individual strains can respond very differently to different physicochemical processes, and extrapolation from one strain to another should be carried out with extreme caution, unless there are robust parallel studies that allow direct comparisons (EFSA BIOHAZ Panel, 2020a). This also applies to prions derived from naturally occurring TSE.…”
Section: Rml Strainmentioning
confidence: 99%
“…An additional problem is the source of collagen, which may be associated with an increased risk of transmission of zoonoses. In the case of collagens of porcine and bovine origin, there is increased risk of the transmission of bovine BSE 94,95 …”
Section: Introductionmentioning
confidence: 99%
“…In the case of collagens of porcine and bovine origin, there is increased risk of the transmission of bovine BSE. 94,95 Of course, the simplest solution would be to use human ECM proteins, but to date, there are no effective biotechnological methods for their production. Currently, the only way to minimize the risk of such complications is to replace the entire native human protein with peptides or a set of peptides with a structure corresponding to the fragments that determine the properties of the proteins.…”
Section: Introductionmentioning
confidence: 99%